Evaluation of Current and Post-Development Carrying Capacity of Tigris River Reach in Mayssan Province - Al-Naemi, Maysam Qawmee; Al-Juhaishi, Mohammed Rashid (Al-Nahrain Journal for Engineering Sciences, 2023)
The study aims to evaluate the current flood carrying capacity and its change after some cross sections developments for the 110 km reach of Tigris River and Kmait flood escape system. This reach extends from Ali Al-Gharbi station to Amarah Barrage station. The model is calibrated by using set of data at the Ali Al-Garbi gaging station, that includes flow varied between 790 to 470 m3/s during April 2019. Manning’s n coefficient value of (0.03) is selected as it has the minimum least-squares root difference of (0.148) between the measured and estimated water levels. The results show that the current capacity of Kmait flood escape and this Tigris River reach are 280 m3/s and 1100 m3/s,  respectively.  According to the study of strategic for water and land resources in Iraq, 2014, scenarios are conducted for some cross sections development to improve the capacity of the reach to 2750 m3/s. Results of applied development show that Tigris River can safely accommodate a flood wave of 2750 m3/s when modifying the cross-sections in different locations, and raising the banks level in three locations, 0+00,  79+00 and 95+00km. Earthworks volume of development of the reach is 247603200 million m³, with the total cost of 490 billion IQD.